2019
DOI: 10.1108/ijse-07-2019-0440
|View full text |Cite
|
Sign up to set email alerts
|

Does inward remittance lead to export performance in South Asian countries?

Abstract: Purpose The purpose of this paper is to empirically investigate whether inward remittance leads to export performance in selected South Asian economies over the time period of 1993–2017. Design/methodology/approach The stationarity of the variables is checked by Levin, Lin and Chu t, Breitung t-stat., Im, Pesaran and Shin W-stat., ADF–Fisher and Philips–Perron–Fisher panel unit root tests. Panel Granger Causality is used to verify the short-run causality. Pedroni’s, Kao’s and Johansen–Fisher panel cointegrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…This result is consistent in all specifications of the model as can be seen in column (2), (3), and (4), however in slightly different magnitudes. Our finding for this variable is in line with the literature and supports to the findings of Jena and Sethi (2020) and others in the literature.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent in all specifications of the model as can be seen in column (2), (3), and (4), however in slightly different magnitudes. Our finding for this variable is in line with the literature and supports to the findings of Jena and Sethi (2020) and others in the literature.…”
supporting
confidence: 93%
“…Shamim et al (2015), detects the negative effect of remittances on export performance in the long run using the annual data from Pakistan. Jena and Sethi (2020), using the annual data for South Asian countries for the period of 1993-2017, suggest that remittance inflows are affecting export performance negatively during the study period.…”
Section: Cooperatives and Export Performancementioning
confidence: 94%
“…They found that that FDI and remittances have a significant impact on economic growth in India, whereas in Sri Lanka, foreign aid and remittances play an important role in enhancing economic growth. Similarly Jena and Sethi (2019a) empirically investigate whether inward remittance leads to export performance in selected South Asian economies over the time period of 1993–2017. They found that inward remittance is affecting export performance negatively during the study period.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Different types of indices of financial development are used to illustrate the possible impact of financial development on human development. In this paper we use domestic credit to private sector percentage of GDP as proxy of financial development (Colombage, 2009; Jena & Sethi, 2019; Kar, Nazlıoğlu, & Ağır, 2011; Khan & Senhadji, 2003; Zaman, Izhar, Khan, & Ahmad, 2012).…”
Section: Data Sources and Methodologymentioning
confidence: 99%
“…found that financial globalization and trade openness have a positive and significant influence on economic growth. SimilarlyJena and Sethi et al (2019) empirically investigate whether inward remittance leads to export performance in selected South Asian economies over the time period of 1993-2017.…”
mentioning
confidence: 99%